La transmisión de los epigramas damasianos (ss. IV-X) - Warburg, Inés (2008)
La presente contribución tiene como finalidad examinar las diversas formas y circunstancias de transmisión de los epigramas damasianos desde que se colocaron en los cementerios suburbanos por voluntad del obispo de Roma en el s. IV hasta las primeras colecciones manuscritas de la época carolingia (ss. VIII-X)
The aim of this contribution is to examine the different forms and circumstances of transmission of Damasus' epigrams that were placed in suburban cemeteries by the wíll of the bishop of Rome in the fourth century until the early manuscript collections of the Carolingian period (eight century to tenth century)
Keywords: Dámaso; Epigramas; Transmisión; Epigrafía métrica; Poesía tardoantigua; Damasus; Epigrams; Transmission; Metrical epigraphy; Late antiquity poetry; Filología; Epigramas; Dámaso; Poesía